Hair Barrette Induced Cochlear Implant Receiver Stimulator Site Infection with Extrusion - Trung N. Le; Jordan Hochman; Darren Leitao (Case Reports in Otolaryngology)
Background. Cochlear implant infections and extrusion are uncommon but potentially devastating complications. Recent literature suggests conservative management can be employed. Local measures inclusive of aggressive surgical debridement with vascularized flaps and parenteral antibiotics represent a viable option and often permit device salvage. However, explantation should be considered if there is evidence of systemic, intracranial, or intractable infection. Method. A Case report and literature review. Case Report. This case illustrates a complicated local wound infection associated with cochlear implantation due to transcutaneous adherence of a ferrous hair barrette to a cochlear implant magnet. Reconstruction of computed tomography (CT) data with 3D volume rendering significantly improved the value of the images and facilitated patient counseling as well as operative planning. Conclusion. Cochlear implant infections can be associated with foreign bodies. CT images are beneficial in the evaluation of cochlear implant complications. 3D CT images provide a comprehensive view of the site of interest, displaying the relationship of the hardware to the skull and soft tissues, while minimizing associated artifacts. Cochlear implant patients should consider use of nonmetallic hair devices.